Estudo da produção de biossurfactante em caldo de fermentação - Bueno, Silvia Messias [UNESP]; Silva, Adriana Navarro da [UNESP]; Garcia-Cruz, Crispin Humberto [UNESP] (Sociedade Brasileira de Química, 2010)
A bacterium isolated from soil contaminated by hydrocarbon was studied and, by biochemical tests and analysis of PCR, the presence of Bacillus pumilus was identified. The production of biosurfactant was optimized, test of oil degradation and antimicrobial activity determination. The results showed that pH 5.0 and 7.0, 72 h of fermentation, sucrose and sugar cane juice (2%) had best yields. The bacterium is able to degrade crude oil and displays bacteriostatic and fungistatic activity. From the analysis of proximate composition of biosurfactant found the presence of biopolymer formed by a lipopolysaccharide-protein complex.
Study on the production of biosurfactant fermentation broth
Keywords: biosurfactant; microorganism; fermentation